Vous êtes sur la page 1sur 85

# .

aun + b

= . n +1

.I

.II
.III
.IV
.V

( a 0) un+1 = aun + b :

.VI
.VII

)+(

.VIII ) + (
.IX ) (

:

.
" "
" "
.

" "
.
. :
" ....

.

".
:
n

i 2 = i + i (i - 1)
i= 2

i =1

1174

i =1

.I

A 130

B2%

A 6000 B

un

2005

vn

.2005+ n

(1 u0 v0 u1.v1

u n+1

(2

. un

(un )

.r

(3 un

.n

v n+1

(4

.vn

(vn )

.q

(5 vn

.n

(6

A B

. 2010

6000 . 2005
(1

u0 = 6000 v0 = 6000
u1 v1 2005 + 1 . 2006

130

(.

## = 6000 (1 + 0, 02) = 6000 1, 02 = 6120

)

2%

2005+ n

100

.(

(2

130

v 1 = 6000 + 6000

un

un +1 = un + 130

(un )

= 130

(3 n

6000 + 130 n

(4

(vn )

2%

= .un

= 1, 02
n

(1, 02)

(5 n

.r

2005+ n

vn

vn +1 = 1, 02 vn :

.q

.vn = 6000

(6 :

u5 = 66506624

.v5

(un)

r) r

. un +1 = un + r :n

(un)

= 2n + 7

:
u n 2

u n+1 = 2(n + 1) + 7 u n +1 - u n = 2 u n +1 = u n + 2

u0 u 0 = 7

(vn)

5 v 0 = 17

v 1 = v 0 + 5 = 17 + 5 = 22 : v 2 = v 1 + r = 22 + 5 = 27

v 3 = v 2 + r = 27 + 5 = 32

...

= u 0 + nr

(un)

u0

un

. u n

u1

= u 1 + ( n - 1)
r

. u n

)(

(un)

: p

un = u p + ( n - p )r

(un)

u20

4 -5

n = 20= 2

= u2

= u p + ( n - p )r

. un

p. u 20 = u 2 + 20 - 2 r = -5 + 18 4 = 67:

( n+1)

(un)

SS = u 0 + u 1 + ........+ u n -1 + u n :

u0

. un

u 0 +un
2

S = u 0 + u 1 + ........ + u n -1 + u n = ( n + 1)

:
+
) S = (
2

= 1 + 2 + 3 + ...+ n

S
.1

1+ n

S = 1 + 2 + 3 + ...+ n = n

2
(un) 3

21

= u 0 + u1 + ...+ u 20

u0

. u0 = 5

) ( 20 + 1:

5+ u20
2

S = u0 + u1 + ... + u20 = ( 20 + 1)

= u0 + 20r = 65

u20

5 + 65
= 735 :

= 21

.S

( un)
(1

= -3n + 2 :

.u n

u1. u2

(2 ( un)

(3

S = u1 + u 2 + ........+ u n :

u 0 = -3(2) + 2 = -4 (1

(2 : ( un)

u1 = -3(1) + 2 = -1

n u n +1 - u n

. r

= -3 ( n + 1) + 2 - [ -3n + 2]= -3

. u n +1 - u n

( un) = -3

.r

(3 . n

-1 - 3n+ 2
:

n (1 - 3n)
2

=n

u 1 + un
2

S =n

.S

ba

a + c = 2b

. c

79 60 41

2 60 :

= .79 + 41

(un)

q) q

un+1 = un q :n

(un)

0,5 3n

u n +1 = u n 3

= un 3:

= . un+1

(un)

u 0 = 12

1, 5

u0

## u1 = u 0 q = 12 1, 5 = 18u 2 = u1 q = 18 1,5 =27

= u 2 q = 27 1,5 = 40,5

. u 3...

(un)

= u 0 q n :

. u n

u0

un

u1

= u 1 q n-1

. u n

(un)

un = u p q n- p :
n p

(un) 1, 5 . u4 = 3
u10

n = 10p = 4

un = u p q n - p= u4 q10- 4 = 3 2 6 = 192:

( n+1)

. u10

(un)

1- qn+1

1- q

S = u0 + u1 + ........+ un -1 + un = u0

) = (

(un) 3

0,5

= . u1

.S

1- qn

1- q

S = u1 + ........+ u10 = u1

1 - 310
= 14762
1 - 3

= 0,5

= 10

.( n

.S

= 1

q:

S = u 0 + u 1 + ........ + u n -1 + u n = ( n + 1)
u 0

bac

= b 2 :

. a c

. c

256128

512

## 128 512 = 65 536 = 256 2 :

(vn )
= 2

v 1 = 3

.q

(1

v2

.v3

(2 n .vn

(3

n = v 1 + v 2 + ........+ v n

.S

= v 2 q = 6 2 = 12 v 2 = v 1 q = 3 2 = 6 (1

= v 1 q n -1 = 3 2n-1

(2

.v 3

.v n

(3 . n

1- qn

1- q

= v 1 + v 2 + ........+ v n = v1

1 - 2n
= -3 (1 - 2n ) = 3 ( 2n - 1)
1 - 2

.S

S = 3

3000 20053630

. 2007

(1
(2

.a

2030

.
:

= 1+ a

.q

(1

un

2005+ n

u 0 = 3000

(1+ a )u n

. u n +1 = u n

(un )

u0

+ 1)

. 2005 + ( n

. u 2 = 3630

+ au n

u n+1

un u n+1

= . u n +1

q = 1+ a

. u 0 = 3000

u0 2005 + 0

u1 2005 + 1
u2 2005 + 2

u 2 = u 0 q 2

q 2 = 1, 21 : = 1,1

(2

2005 + 25

u2
u 0

25

(1,1)

. q
. q

= 0,1 = 10%

.a

2030

= . 2030

= u 0 q 25

. u 25

u 25 = 3000 . u 25 32504,12

u 25 = 32504

32500 2030

32504

.II

) (un

n+ 1
:
2 n +3

= un

(1
.

...

n
un

(2 ).(un

(3

1
1
u n2
3

(4

(5

. u n -

x + 1
2 x +3

=f ( x)

(1 n

un

0,6
0,5
0,4
0,3
0,2
0,1
0
14

16

(2

12

10

(un)

1
1
0 u n(3
2
3

0 <u n -

1
1
u n
:

3
2

. <

(4 : f

x 00

+
1

f ( x)

2
1
3

(5 .

.I

(un )

m M

.1 ( un)

. un M

.2 ( un)

. un m n

.3 ( un)

. m un M

m M

(un)

un = 2+

n *

5
4,5
4
3,5
3
2,5
2
1,5
1
10

12

.
:

n 1 1

2 + 3

.2+

. u n 5

(un)

. 5

n 1

(un)

> 0

> 2

. u n

. 2

5
5

) . (un

.II

) . (un

(un )

: un

( )

.u n +1 u n n
.1

.u n +1 u n n
.2

.u n +1 = u n n
.3
.4

(un )

n n 0

(un )n n

.n

.
n

. (un )

(un )

1
= -
2

= k n

. u n

. u n

1
2n +1
:

n 2 + 4
2

( un)

= . un

) (un . 2

(un)

( m :

) ( un - m.

un - M

f [ 0 + [

un = f ( n )

: un - 2

2n +1
2n + 1- 2n2 - 8
-7
un - 2 = 2
=- 2
= 2
2
n +4
n +4
n + 4
-7
-7
. 2
2 < 0 :n

n + 4
n + 4
2

(un)

. u n - 2 < 0 : . u n < 2

. 2

n + n+ 9
:

n
2

( un)

) (un . 7

( n- 3)
n

=un - 7

n * . u n - 7 0 7

. u n

= . un

(un)

. 7

( un)
2 n-1
n + 3

= . un

(un):

. un +1 - un

un+1
un

1 .

[ 0 + [

un = f (n)

un = f (n) f
2 x- 1
=. f ( x)
[ 0 + [:
x + 3
f [ 0, + [:
)2( x + 3) - (2 x-1)(1
7
=f '( x)
=
2
)( x + 3
( x + 3)2

xf ( x )> 0 [ 0 + [

f [ 0 + [
( un).

( un)
2 n-1
2n

5
6

3
4

1
2

un = ...

un+1

un
un+1

un

.1

)1 3 5 ... ( 2n - 1) ( 2 ( n+ 1) - 1
)2 4 6 ... 2n 2 ( n+ 1
1 3 5 ... ( 2n- 1)
2 4 6 ... 2n
2
n
+
1
1
( ) = 2n+ 1 :
un+1
.
=
un
2 ( n + 1)
2 n + 2

un+1
=
un

2 n+ 1
2n + 1 < 2n + 2< 1
2n + 2

u
. n+1 < 1
u n

. u n +1 < u n n

( un)

.III

( un)

n 1

un = 2+

(1

un n

(2

(1

un

(2

= 2

.l

## 2 + 106 <un 106> n

< 2

.10

> n

1
< 0 10- 6 <
n

106

2+106
un
2

n
Un
3
1
2,1
10
30 2,0333333
2,02
50
2,01
100
2,002
500
2,001
1000
2,0001
10000
100000 2,00001
1E+06 2,000001

1E +06 1106

un

( un)

un = 2

l = 2

l = 2

. lim

n+

.1

un (un)

(un) l n + (un)

. l

limu n = l

n+

(un)
un = 3-

.3

-1

n
n

( 0

( -1)

.
.2

)u n =f ( n

) (

(un )

. +

= f ( n )

u n

[ 0 + [

lim f (x )= a

x+

limu n = a

n+

1
lim 3 - = 3
n+

3 - 1 = 3
x+

. lim

.3

f ( n)

. +

(un )

:r

.1

0 > r. lim un = +

.2

0 < r. lim un = -

.3

n+

n+

r = 0

(un )

lim un = u0

n+

. un = u0 + r

[ 0 + [

. :

0 > r

lim f ( x)= -
-

r = 0

f ( x)= +

lim

x+

0 < r

x+

f :x a rx + u0

n un = u0

lim un = u0

n+

(un )

: 0 > q

1 > q

lim un = + . 0 >u0

lim un = - . 0 <u0

n+

n+

- 1 < q < 0

lim un = 0

n+

. u n = u0 q

lim q x = +

n+

f :x a u0qx

1 > qlim q x = 0

n+

. 1 < q < 0

= 1

q n

lim un = u0

n+

un = u0 1n = u0

(un )

.4

) (

.1
.2

(un )
n
u n = ( -1) .

1
1
+ 3 :

(un )
2n
1
u n +1 - u n = n+1 : u n +1 - u n > 0
*
2
1
1
- n < 0 :- n + 3 < 3
* 2
2
2

u n = -

u n < 3

(un )

1
lim - n = 0
n +
2

.0

(vn )

.5

1
+ 5
3n

= v n

(un)

:
n

2n 2 - 5n+ 1
= un
n 2 + 5

(un)

( n )

u n = f

2x - 5x +1
x 2 + 5
2

[ 0 + [

= 2

2x2

x2

## lim f ( x)= lim

x+

x+

=( x)

.f

un = 2

. lim

n+

) (un . 2

(un)

1
n + 2

u n = 2n+

u n = f ( n )

1
:
x + 2
1

lim
= 0
x+ x + 2

( x )= 2x +

[ 0 + [

.f

2x = +

. lim

x+

f ( x)= +

. lim

x+

un = +

. lim

n+

:(un)

3
) (un

2
3

=q

= . u 0

= u 0 + u 1 + ...+ u n :n

. S n

.1

n ).(un

un

.2

Sn

n . Sn

2
.1 = u 0 q n = 2 n
3
n
2
2

## 0 < < 1 . lim = 0

n +
3
3

lim u n = 0

n+

(un)

.
.0
n+1

2
1-
n+1
1- q
3
S n = u0
= 2
2
1- q
13

.2 n

2 n+1
. S n = 6 1-
3

2
< 1
3

n+1

< 0

lim S n = 6

n+

. u n

= 0

2
. lim

n +
3

.IV

Sn

S n = 1 + 3 + 5 + ... + ( 2n -1)
:

.1 S2 S1 .S3
.2
:

.
-

(\$A\$1: A1) : B1

SOMME

= SOMME

- B1

.Sn

.3 .
.4 .

P ( n)

a n b n

a n = 1 + 2 + 3 + ...+ n

b n = 13 + 23 + 33 + ... + n 3

.1 a n

.n

.2

.
(

( n)

(
(

P ( n)

P ( n)

+ 1

.P

n = 2 n = 1= 3

n n 1

.n

P ( n)

S2 = 1 + 3 = 4 S1 = 1 .1

.S3 = 1 + 3 + 5 = 9

.2

## = SOMME (\$ A \$1: A1)

.n

B .

Sn

1
4
9
16
25
36
49
64
81
100

1
3
5
7
9
11
13
15
17
19

.3 :

S1 = 12 = 1 S2 = 22 = 4 = 9

S3 = 3 ...

n 2 n 1

= .Sn

.4 Sn:

= 1 + 3 + 5 + ... + ( 2 n - 1)

2n 2
= n :

2

.1

S n

. 1

(1 + ( 2n- 1) )
2

= . Sn

= . Sn

1+ n
2

a n = n

1 .1
.2
( :

n = 10

b1 = a1 = 1

b1 = (a1) 2

b10 = (a10) 2

n 1

bn

an

1
3
6
10
15
21
28
36
45
55

1
2
3
4
5
6
7
8
9
10

1
1
9
8
36
27
64 100
125 225
216 441
343 784
512 1296
729 2025
1000 3025

b1 = a1 = 1 b 2 = (a 2) 2 b 3 = (a 3) 2

P ( n)

= (a n )2

.b n

1+ n
2

P ( n)

a n = n 1

n 2 (n + 1)2
= . b n
n 1
4
( P ( n) n = 2 n = 1n = 3

12 (1 + 1)2
n 2 (n + 1)2
= b1
=1 :

4
4
32 (3 + 1)2
22 (2 + 1)2
= b3
= b 2 = 36
= 9
4
4
.
(

P ( n)

n 1

+ 1

.n
2

(n + 1) 2 ( (n + 1) + 1)
4

n 2 (n + 1)2

4
(n + 1)2 (n + 2)2
= b n+1
:

4
n 2 (n + 1)2
= . b n
4
b n+1 = 13 + 23 + 33 + ... + n 3 + ( n + 1)3
= b n

b n +1 = b n + ( n + 1)3

n 2 (n+ 1)2
bn+ (n + 1)3 :
4

= b n+1

(n+ 1)2 2
( n + 4(n + 1)) :
4
(n+ 1)2 2
= b n+1
( n + 4n + 4) :
4

= b n+1

= b n+1

(n + 1)2 (n + 2)2
4

= b n+1

( :
:

P (n)

3 2 1

P (n)

n +1

P (n)

. n

P (n)

.1
.2

P(0)

P (n)

P (n)

. n + 1

P (n)

n n0 :
.1
.2

P ( n0)

P (n)

n n0 . n + 1

n ( n+ 1)
n 1
2
. P (n)

= 1 + 2 + 3 + ...+ n

P(1)

1 2
:
n = 1
2

P (n)

n ( n+ 1)
n 1:
2
P ( n + 1)

=

= )+ ( n + 1

. 1 + 2 + 3 + ... + n

1 + 2 + 3 + ... + n + ( n + 1) = (1 + 2 + 3 + ... + n ) + ( n + 1)

n ( n+ 1)
2

)n ( n+ 1
+ ( n + 1)
2

= 1 + 2 + 3 + ...+ n

( n+ 1) n + 2 :
(
)
2

.1 + 2 + 3 + ...+ n

( n + 1)( n+ 2)
:

=1

) (

= )1 + 2 + 3 + ... + n + ( n + 1

= )1 + 2 + 3 + ... + n + ( n + 1

n 1

n ( n+ 1)
2

.1 + 2 + 3 + ...+ n

n 3 - n

. 3

n3 - n "

" n

.
:

-0

03 - 0 = 0 = 30 n = 0

0 .3

. n = 0
:

n3 - n :

(n + 1)3 - ( n + 1)

n + 1

- n = 3k

.3

n3 = 3k + n

(n + 1) - (n + 1) = n3 + 3n 2 + 3n + 1- n -1 = (3k + n) + 3n 2 + 2n
3

(n + 1) - (n + 1)= 3k + 3n 2 + 3n = 3(k + n 2 + n)
3

3(k + n 2 + n) 3 (n + 1) - ( n +1)
3

.3

n3 - n n

. 3

:
:

an = n 3 - n

an+1 = ( n + 1)3 - ( n + 1)

an 3

an +1 - an 3

an +1 3

## an +1- an = (n + 1)3 - (n + 1) = (n + 1) ((n + 1)2 -1))

an +1 - an = ( n + 1)( n 2 + 2 n ) = n 3 + 3n 2 + 2n

an +1 - an = ( n + 1)( n 2 + 2 n ) = ( n 3 - n ) + 3( n 2 + n )

an +1 - an

3 .

(un )

u0 = 4

1
u n +1 = 2u n - 1 n

.1

(un )

.2

(un )

.
. -2

.1 (un )
u n +1 u n

. un +1 - un 0

: u1 = 4 - 1 = 1
2

.n = 0

u 0

. u1

n 0
u n+1

. u n +1 u n

n + 1

.u n +2

. u n +1 u n

) (

1
1
u n +1 - 1 u n - 1
2
2

u n + 2 u n+1

. n + 1

: . u n +1 u n n

(un )
.2 (un )

-2

n -2

. u n

u 0 = 4

-2

. u 0

. n = 0

-2

-2

u n n + 1

. u n+1

u n -2

1
( -2 )- 1
2

1
2

u n - 1 u n+1 -2

. n + 1

(un )
(un )

-2 n

. u n

. -2

.V

:( a 0) un+1 = aun + b :

2000

5%

10 000 DA

. 2000 DA

un

.2000+ n

.1 u0 n

un + 2000
.2

.un +1 = 1, 05

(un )

.3

( (vn )

v n = u n +40000 n

. n

2010

000 .1

.1, 05 vn

. u0 = 10

5
+ 2000
100
= 10 000 (1 + 0, 05 )+ 2000

u1 = 10 000 + 10 000

= 1, 05 u0 + 2000

un

u2 = 1, 05 u1 + 2000

...

un + 2000 n

.2(un )

aun + b :

.un +1 = 1, 05

= . un +1

b .

## .3 vn +1 = un+1 + 40 000un +1 = 1, 05 un + 2000

vn +1 = 1, 05 un + 2 000 + 40 000

vn

.:

2 000 + 40 000
= 1, 05 ( un + 40 000)
1, 05

1, 05

. v0 = 50

. vn +1 = 1, 05 vn

( vn )
000

vn +1 = 1, 05 un +

un

:n

## un = vn - 40 000 = 50 000 1, 05n - 40 000

000 1, 05 n - 40 000

.4 2010

## 000 1, 0510 - 40 000 ; 41 445

.u n = 50

445 DA :

. u 10 = 50

.u10 ; 41

(un )

0) u n +1 = au n + b

(a

u0 n

un+1 = aun + b

u n +1 = f (u n)

.a

a ax + b

.x

a = 1 :

(un )

. b

. u n +1-u n = b n

:
-

b < 0(un )

b > 0(un ) -

b = 0

(un )

= u 0 + bn

. u n

b < 0limu n = -

n+

> 0

limu n = +

n+

a 1 :

(un )

u n +1-u n

. n

= a (u n -u n-1)

## u n +1 - u n = (au n + b ) - (au n-1 + b ) n

. u n +1 - u n

u n +1 - u n = a (u n -u n-1)
u n -u n -1 = a (u n -1 - u n-2)
u n -1 - u n -2 = a (u n -2 - u n-3)
...
...
...

u 3 - u 2 = a (u 2 - u 1)
u 2 - u1 = a (u1 - u 0)
:

u n +1 - u n = a n (u 1 - u 0)

- a > 0

u1 -u 0 (un )

- a < 0

(un )
.

u n +1-u n

an

(un )

(un ) u n +1 = f (u n)

(un )

u1 > u 0

< u 0

u1

(un ) (vn )

:
n

b
1- a

= un -

.v n

= u 0

. u1

ab
b

= a u n = avn
1- a
1- a

(vn )

= au n -

b
1- a

b
1- a

= vn +

> 1

lim u n = -

-1

b
1- a

.v0

= v 0 an +

lim a n = 0
-1 < a < 1

.v n

. u n

b
1- a

= lim un

n+

lim a n = +

n+

lim u n = +

n+

.v0

n+

b
1- a

1- a

= v 0 a n n

n+

(un )
-

u n

= au n + b -

v n +1 = u n +1 -

(a )

(un )

(un )

a > 1 -1

.a

(un )

1
un + 2
3

u 0 = a

= .u n +1

.1 = 3

.a

( u2u1 . u3 (un )
.

( (un )

.2 a = 2 ( vn)

= un - 3 :

( ( vn)

. vn

( vn n un

. n

( (un )

( )

( . un

.3 . a = 6 (un )

.1
(

=3

a. u 0 = 3 :

u 2 = 3 u1 = 3 :

(un )

. u 3 = 3

= 3 n

= 0

n. u 0 = 3

+ 1

un+1 = un + 2
3
1
3 + 2 = 3
3

.n

) (

u n = 3

. u n

u n+1 = 3

= . u n+1

+ 1

.n

. n (un )

( (un )
.2

.3

a = 2u 0 = 2 :
1

( v n +1 = u n +1- 3 = u n + 2 - 3 = u n - 1 = (u n - 3)
3
3
3
1
vn
3

= . vn+1

( vn)

1
3

=q

. v0 = -1

(v 0 = u 0 - 3)

1
.v n = v 0q = -
n
3
n

1
u n = v n + 3+ 3
3
n

(un )

1
< 1
3

. u n = -

1
lim . lim u n = 3
= 0
n+
n +
3
n

< -1

. 3

( u n +1 = f (u n ) f : x a x + 2
3
2
1
> 0 u 1 - u 0 = u1 - u 0 >0 (un )
3
3

.3

=6

a. u 0 = 6 :

1
3

> 0 u1 - u 0 < 0

(un )

(u1 - u 0 = -2)

.VI

.1 (un )
* (un )

:r

.1 0 > r. lim un = +
n+

.2 0 < r. lim un = -
n+

.3

*(un )

r = 0

: 0 > q

1 > q

lim un = + . 0 >u0

lim un = - . 0 <u0

n+

n+

1 < q < 0-

(un )

lim un = u0

n+

lim un = 0

q = 1(un )

n+

lim un = u0

n+

* .
* .
.2
*

P ( n)

:
-

*
.1
.2

P (n)

P(0)

P (n)

.n + 1

.3

*

un+1 - un

:

* .
.4

.1
.
.2
.

.3

q q ]-11]

.VII

) 12

(.

2005

.1

100 000

un

3%

2005+ n

u0 u1. u2

( . u n +1 = 1, 03 u n n

(un )

( n

. un

2025

2010

) (.

.2

200 000

5000

vn

2005+ n

.
( v0 v1.v2

( v n+1
.vn (vn )

un

. n

2025

2010

) (.

200 000

.1
( u0

2005 + 0

2005

. u0 = 100000
.3%

3
= 100 000 1,03 = 103000
100

## u1 = 100 000 + 100 000

. u2 = 106 090 :

un

un+1

2005 + ( n + 1):

3
= u n (1 + 0, 03 )= 1, 03 u n
100

2005+ n

un+1 = un + un

. 3%

( un)

1, 03

. u0 = 100000

( (un)

un

= u 0 q n :

(1, 03)

u0

. u n

. un = 100 000

( :

115927

(1, 03)

2010

. u5 = 100 000

180 611

20

(1, 03)

2025

(
.

200 000
2005 + 24

.2029

155796,742
160470,644
165284,763
170243,306
175350,605
180611,123
186029,457
191610,341
197358,651
203279,411
209377,793
215659,127

15
16
17
18
19
20
21
22
23
24
25
26

.2
( v0

5000

vn

v n+1

2005+ n

2005 + ( n + 1):

vn+1 = vn + 5000

(vn )

5000

. v0 = 100000

( (vn)

v0

vn:

v0 + nr

= . vn

( :

2010

2025

## v20 = 100000 + 5000 20 = 200 000

(
. 2025

200 000

(un )
u 0 = 0

u n +1 = 2u n + 1 n

un
.1

1 . 0

B20

= 2* B 2 + 1 :C2

C2

.
.

= B2 + 1 :B3

u n + 1

. u n+1

B3 .

.2 u n + 1

n un

. n

un

. n

(vn )
= u n + 1

.v n

.1 (vn )

.2 vn

un

.n

.3 .

.1 :

.2 2

(u n + 1)

2n

u n + 1 = 2n u n = 2n - 1

n = 0 2 0 - 1 = 1 - 1 = 0

u n = 2n - 1

= 0

= . u 0

.n

. n + 1

u n+1 = 2 n+1 - 1

u n +1 = 2u n + 1

u n +1 = 2u n + 1 = 2(2n - 1) + 1 :
un

## u n+1 = 2(2n - 1) + 1 = 2 2n - 2 + 1 = 2 n+1 - 1

. n + 1

= 2 n - 1 n

. u n

(vn )

n= u n + 1 :

.v n

: n

v n +1 = u n +1 + 1 = (2u n + 1) + 1 = 2 (u n + 1)= 2v n

(vn )

vn

un

= 2n

.v n

= u 0 + 1 = 1

.v 0

u n = v n - 1

u n = 2n - 1 n

(un )
u 0 = 6

.1

.u n +1 = 3u n - 10 n

.2 u n - 5 n un

.n

.3

.1

n 0 1 2 3 4 5 6
7
8
9
10
un 6 8 14 32 86 248 734 2192 6566 19688 59054
un5 1 3 9 27 81 243 729 2187 6561 19683 59049

.2

un - 5

: . u n - 5 = 3 n

: n

+ 5

. u n = 3

n = 0 + 5 = 1 + 5 = 6

= 0

. u0 = 3
.n

. n + 1

. un +1 = 3un - 10
:

. n + 1

+ 5

. u n = 3

(vn )

n= un - 5 :

. vn

: n

## vn+1 = un+1 - 5 = 3un - 15 = 3 ( un - 5 )= 3v n

(vn )

= u0 - 5 = 6 - 5 = 1

. v0

vn

. vn = 3

un = 3n + 5 n

un

(un ) .1

u0 =70 . -5

= u 0 + u1 + ... +u13

.S

## (un ) .2 (vn ) . r(wn )

v n = 3u n - 1

w n = u 2n + 3

(vn )(wn )

.3

[ 0 + [

x
f ( x )

3
-1

(un )
(

u0

u n = f ( n )

( (un )

.4 f

[ 0 + [ C f

.
y

Cf

(un )

u n = f ( n )

:
(

u0

( (un )

.5 f [ 0 + [
(un ) . u n = f ( n )

(
(

(un )

( (un )

f ( x )= x 2 - 2x

.6 (un )

1- n2

un =

(1 u n +1 - u n (un )

(2

f= f ( n )

. u n f

.7 (un )
(1

4n

n 2

un =

un+1
u n

(2 (un )

.8 (un )

u n = 2n :

(1 n

(2 (un )
.9 (un )
.1(

.3

2
.u n =
3

1
*
:

n +1

(un )

= un

( . un

( (un )
.2

. S n = u 1 + u 2 + ...+ u n Sn

.10 n

n ( n + 1)( 2n+ 1)
6

= 12 + 22 + 32 + ...+ n 2

lim S n

n+

(un ) .11
u 0 = 3

(un )

2u n - 3 n

= . u n +1

.12

23n - 1 n

. 7

.13 2000

500 DA

50 DA
.

u1

un

.n

(1 un

.n

(2 2007
(3 31 2007
.14

32000 L

10

5000 L
.

10

45,4

.15 1990

52,6 .2002
v0

1990 vn

.r

(1 .r
(2 2020

.16 p0

(1

p1

pn

5%

p2

.p0

(2
.17

5000 DA

(1 . 150 DA

un

. n

( . u2
(

un

u8

( .
(2 . 3%

vn

(
(

v2

vn

.v8

( .
(3 .

.18 (un )

[3 + [
x - 1
2 x -5

n- 1
2n - 5

= un 1

=f ( x )

.1( f

[3 + [
(

f ( x ) 2

lim f ( x )= l

x +

1cm

f ( x )- l x

[3 + [

f ( x ) l

4 cm

(un ) 2

.1( (un )

( f (un )
.19

= u 0

un
u 02

unn

( (un )
.2 (un )

= .un+1

.2( (un )

.n

. 2

.20 u2 , u1 u3(un )
u 0 = 2

.u n +1 = 0,9u n - 13

a .21 . (un )
u 0 = a2,5u n - 1,5

= . u n +1 :

a = 0 (un )

a = 1 (un )

( a = 2 (un )
( un ).22

3n
= un
:

n +2

(1 .

(2
(3

- 1

> 0 n

.un

un+ 1
u n

(4 ( un )

.23 .0, 7

(1

p n = 1 - 0,3n 1

.n

(2 ( pn )

(3

pn

.0,999
.24

4%

2000

.1( .

( un

un

. n

. n

( . limu n
n+

.2( )(

pn n

. n

pn

4000

.25
.1(

+ 2 2 + 32 + ...+ n 2

Sn = 1

s3 s2 s1s4

( s n+1

. n

.2

n ( n + 1)( 2n+ 1)
6
.26

= Sn

n:

Sn = 1 + 2 2 + 3 2 2 + 4 23 + ... + ( n - 1)2n- 2

Sn = ( n - 1)2n - n 2n -1 + 1 = 1 + n - 1 2n
2

(un ) .27

2+ u n n

u 0 = 1

= .u n +1

(1 2 n

(2 (un )

u n +1 = au n +b :

1
.28 (un ) (u n - 1) :
3
(1

u0 (un )

(2 u 0 = 4= 2u n + 1

(vn )

vn

.0 u n

= .u n +1

.v n

.v0

un

( (un )

( un ) .29 u0 = 1 :
un - 1
2

= . u n+ 1

(1. u3 u2 u1
(2

v n = un + a

( a ( vn )

( vn n un

. n

(3

( un )

(4

( un )

Sn = u0 + u1 + u2 + . . .+ un :

(5 n
Sn
. lim

n+ n
.30

3%

.1

C0

(
(
.2(

400000

C n = 0,8 0,975n y n

( Cn

( (Cn )

3%

Cn yn

.
.

n +

.4 (Cn )
3%

= 1)

.( n

.(n

2,5%

= .y 0

y1C1

y2 = 2) C2

( Cn

.3

80%

S =5 .1

.2 n

## vn+1 - vn = 3un+1 - 1 - 3un + 1 = 3( un +1 - un)

vn+1 - vn = 3r ( un)

. r

( vn)

. 3r

- wn = u2( n+1) + 3 - u2 n + 3= u2 n + 2 - u 2n

. wn +1

u2n + 2 = u2n + ( 2n + 2 - 2n )r

## wn+1 - wn = u2( n+1) + 3 - u2n + 3 = 2r

( wn)

. 2 r

.3( u0 = f ( 0 )= 0

( ( un)
. f ( x ) 3 [ 0 + [

: 3

.4(

u0 = f ( 0 )= 3 :

( ( un)
. f ( x ) -2 [ 0 + [

: -2

.5(

f ( x) 0

+
0
-1

( -1

f ( x ) -1 [ 0 + [

( .

(1 .6

2n+ 1
n ( n + 1)

0<un +1 - un = -

(2

]0 + [

(3

1- x2

=( x)

. f

f ( x)

]0 + [

(1 .7 n

un+1
4 n+1
n 2 2n
=

2
n
un ( n +1)
4 n+ 1

(2

un+1
un

.1 : n 1

u
2n
. n+1 =
1
un n + 1

2 n 2
(1 .8 = n

3n 3
2
= .q
(2 (un )
3

= .u n

## 1 < q < 0un = 0

.lim

n+

.1 .9(

1
:
x + 1

(un ) ]0 + [
-

=f ( x)

x
f ( x)

(un )

( : un . 0 > un n

( (un )

Sn = u1 + u2 + ...+ un

1
1 1 1
1 1
1
= 1- + - + ...+
- +
2 2 3

n - 1 n n n+ 1
1
= 1n + 1

. 2

lim Sn = 1

n+

0 ( 0 + 1) ( 2 0 + 1)
: n = 0
6

.10

= 02

. n + 1

)n ( n + 1)( 2n+ 1

)+ ( n+ 1
6
)( n + 1) ( 2n 2 + 7n+ 6

= )1 + 2 + ... + n + ( n + 1

6
( n + 1) ( ( n + 1) + 1) ( 2 ( n + 1) + 1)
6

=
=

. n + 1

n ( n + 1)( 2n+ 1)
n
6

.11

12 + 22 + ...+ n 2 =

u0 = 3 :n = 0

n . n + 1

un+1 = 2un - 3 : un = 3

) (.

2 3 - 3 = 3

= . un+1

. n + 1

( un)

.12

230 - 1 = 0 :n = 0

n 23n - 1

n + 1 - 1

23n - 1 :7

(2

3 n +1)

. 7

) (.

( k )

23n - 1 = 7k 23n = 7k + 1

- 1 = 23 n 23 - 1 :

(2

23n 23 - 1 = 8 ( 7 k + 1)- 1 = 7 8k + 7

- 1 = 7 ( 8k + 1)

3 n+1)

)3( n+1

.2

k ' = 8k + 1- 1 = 7 k ' :

- 1

3 n +1)

0 . 7

(2

3( n+1)

.2

. 7

. n + 1

23n - 1 n

.7

.13

u1 = 500 (1

. un +1 = un + 50 n

( un)

= 50

.r

. u n = u1 +

(2 un 2007/12/01

= 8 12 = 96

.n

## u96 = 50 96 + 450 =5 250DA :

( S .2007/12/31

u + u
= u1 + u2 + ... + u96 = 96 1 96 = 276 000DA :
2

.S

.14 u1 = 5000

un +1 = un - c n

( un)

u10

. -c
.

## + u2 + ... + u10 = 32 000 :

. u1

2u1 - 9c
u1 + u10
u1 + u2 + ... + u10 = 10 = 32 000

.10

c = 400l :

) (1 .15 : (.

( vn)

v0 = 45, 4

. v12 = 52, 6

= v0 + 12r = 52, 6 :

. v12

= 0,6

: r

0, 6

(2 2020 . v30

## v30 = v0 + 30r = 63, 4 :

2020 63, 4

p1 = p0 + 0, 05 p0 = 1, 05 p0 (1
.16

p2 = p1 + 0, 05 p1 = 1, 05 p1 = (1, 05) p0

( pn)

pn+1 = 1, 05 pn n

= 1, 05

.q

n
(1, 05) p0 n

(2 n

pn 2p0

(1, 05 ) 2

2p0

.pn

n
(1, 05) p0 2p0

p0

.
n

n (1, 05 ) 2

n = 15

:
n

(1, 05 ) 2

ln

ln (1,05 ) ln 2

n ln (1, 05) ln 2

ln 2
ln (1, 05)

= .pn

n (1,05)^ n
1
1,05
2
1,1025
3
1,1576
4
1,2155
5
1,2763
6
1,3401
7
1,4071
8
1,4775
9
1,5513
10
1,6289
11
1,7103
12
1,7959
13
1,8856
14
1,9799
15
2,0789
16
2,1829

ln 2
; 14, 20669
ln (1, 05)

. n 15

15

.17

## .1( u2 = u1 + 150 = 5150DA

( . un +1 = un + 150 n

( un)

.150

. u n = u1 +

## . u8 = 150 8 + 4850 = 9600DA :

8
( u1 + un)=58 400DA
2

= S = u1 + u2 + ... + u8

.2( v2 = v1 + 0, 03 v1 = 5150DA

. vn +1 = 1, 03v
( n n

( vn)

n-1

. 1, 03

(1, 03)

. vn = v1
7

. v8 = 5000

## (1, 03) - 1= 44 461, 68DA

1, 03 -1

S ' = v1 + v2 + ... + v8 = v1

.3 .

.18

.1( : f

f '( x)

1
2

f ( x)

x ( x ) 2 [3 + [
1
(
2
1
4
= f ( x) -
2 2 ( 2 x - 5)
=lim f ( x )

x+

4
2 ( 2 x - 5)

> x ) 0

.f

.
.

[3 + [

[3 + [

1
2

( x)

. f

.19

.1( (un )

un+1 = un n
4

un

: n
n

( (un )

1
un = u0 q = 2
2

.2 (un )

. 2

-11, 2 .20

= u1

## u2 = -23, 08 u3 = -33, 772

.21
(

un+1 = 1,5 ( un - 1)
n

(un )
(

...

## u0 = a = 1u1 = 2,5 1 - 1,5 = 1 :

u2 = 2,5 1 - 1,5 = 1

(un )
(

...

(un )

...

## un+1 = 1,5 ( un -1)

3n
:

( un ).22
n + 2
81
27
9
1
= .u 4
= u3
= u 2
= u0 u1 = 1
(1
6
5
4
2
=

(2

.un

> 0 n

. un

un+ 1
- 1 0 > :
(3
u n

(4 ( un )

.23

(1 . 0,3

= 1 - 0,3n :
n

p n

.n

(2 ( pn ) pn = 1

. lim

n+

(3

= 6 :

.n

.24

u2 = 2000 1 + 2163, 2
.1( u1 = 2000 = 2080
100
2249, 728

= . u4

( n 1

( +

= . lim un
n+

1 - 1, 04n
(
1 - 1, 04

pn = 2000

( lim pn = +

n+

( = 18

.n

n-1

## un = 2000 (1, 04)

= u1

.25

+ 2 2 + 32 + ...+ n 2

Sn = 1

.1( s3 = 14 s2 = 5 s1 = 1
(

. s4 = 12

Sn = 12 + 22 + 32 + ... + n 2 + ( n + 1)

= .sn +1

.2

n ( n + 1)( 2n+ 1)
6

s1 = 1

1(1 + 1)( 2 1 + 1) 2 3
=
n = 1 = 1
6
6

= S1

= Sn

.n

= 1

n
. n + 1

sn+1 = Sn = 12 + 22 + 32 + ... + n 2 + ( n + 1)

)n ( n + 1)( 2n+ 1
2
+ ( n + 1)
6

= sn+1

)( n + 1) ( 2n 2 + 7 n+ 6) ( n + 1)( n + 2 )( 2n+ 3
= sn+1
=

6
( n + 1) ( n + 1) + 1 2 ( n + 1)+ 1
6

. n + 1

n ( n + 1)( 2n+ 1)
n
6

= Sn

.26

n = 2 S2 = 1 2 - 1 22 = 1
2

.1 +

= 2

.n

n . n + 1

1
1
( n + 1) - 1 2n +1 = 1 + 2 n - 2 n = 1 + ( n - 1)2n
2

2
2

Sn+1 = 1 +

## Sn+1 = 1 + 2 2 + ... + ( n - 1)2n - 2 + n 2n-1

1

= 1 + n - 1 2 n + n 2n-1
2

) (

1

= 1 + 2 n - 1 + n 2n-1

2

Sn+1 = 1 + n - 1 2n + n 2n-1

= 1 + ( 2n - 2 ) 2n-1
= 1 + ( n - 1)2n
. n + 1
:

Sn = ( n - 1)2n - n 2n -1 + 1 = 1 + n - 1 2n
2

.27

(1 2 n

. 0 u n

. u 0 = 1 . 0 u0 2

0 u n . 0 un+1 2

x a x

[ 0 +[

2 u n + 2 2 + 2 :
2 un+1 2

.0

2 n

(2 (un )

.0 u n

. un +1 un n

= 2 + u0 = 3 u0

u1 ... un -1 un

un-1 un

[ 0 +[

. u1

un-1 + 2 un + 2

un+1

u0

. un

(un )

u1 ... un un+1

x a x

. u0

u n +1 = au n +b :

1
(1
.28

u0 = -

(2( n

vn+1 = 2un+1 + 1
1

= 2 ( un - 1) + 1
3

2
2
= un - + 1
3
3
2
1 1
1
= un + = ( 2un + 1)= vn
3
3 3
3
1

(vn ) :
3
n

1
(

9 1 1
1
vn = 9 n un = - +
2 3 2
3

= . lim u n
n+

.29
(1

3
1
= u 2 u1 = 0
4
2
(2

:
(

un - 1
+a
2

= un+1 + a

= . u3

. vn +1

= = u n+1 + a

. v0 = 9

. vn +1

vn - 1+ a
:

= . vn+1

( vn )

1
vn n
2

vnn

1
2

=1

.a

= . vn +1

= u0 + a = 2

: v0

1
vn = 2
2

un

: n
n

(3

1
. u n = 2 - 1 n
2

( un )

. un+1 un : ( un )

un+1
un

.1

1 n
lim un = lim 2 - 1 = -1 (4

n +
n+
2

(5 Sn

Sn
= -1
n+ n
lim

- ( n + 1)

n+1

1
1-
2
. Sn = 2
1

1- 2

.VIII

.
(1 .

(un )

( u 0 = -1u n +1 = u n + 0,1
1
(

n + 1
n

. un

2
u n =
3

u
( u 0 = 4 u n+1 = n
2

(2 (un )

( u n = -3n + 1
( u 0 = 4 u n +1 = -3u n

1
(

u n = n +

( u 0 = 1u n +1 = u n +1
(3
.

( un )( vn )

u 0 = 14:

u n +1 = 4 u n + 3 n
v n = u n + 1

( (vn ) 4

( (un )

((vn )

( (un )

.
(1 .
(

lim u n = 6

n+

(un )

( .

( limu = + -u n
n
n+
3

.
( .
( .
(2 .

(un ) (un )

2 n- 3
n + 1
(

(un )

. un

(un )

( (un )
( (un )
(

. 2

1

u n

( (un )
u n = f (n )

2x - 3
x + 1

=f ( x)

.
(1 .
(2 .
(3.

(1
(2

..

. ..

...

. ..

.IX

.1
1

un

2001

5%

10 000 DA

1500 DA

) (.

.2001+ n

.1 u0 . u1

2003

.2 n

= 1 ,05 u n -1500

.u n +1

( )

.3 . un

.4

( (vn )

v n = u n - 30000 n

( (un )

.5

u1 =90000 u 0 = 10000 .1
u2

0, 25 2

.2003

5
u 1 - 1500
100

u 2 = u1 + 7950

= .u 2

0,5

5
10000 - 1500 .2
100

u n +1 = u n +

= 1 ,05 u n -1500

.3

0,5

.u n +1

u n +1 = f (u n )

( x )= 1 ,05 x -1500

.f

(un )

0, 75
.

u1 - u 0 < 0 (un )

.4

(u n -30000)

v n +1 = 1, 05

(vn )

-20000

= .v 0

= 1, 05

## = v 0q n = -2 104 (1, 05)

u n = v n + 30000
n

. v n

.limu n

.5 u 8 = 540,89 -1027

u9

## u n = -2 104 (1, 05 ) + 3 104

= -

v n +1 = 1, 05v n

0, 75

= . u 9

2010 / 01/ 01

.2010

.2
2005

1500

10 %

100

un

. 2005+ n

.1 2006/01/01

.2 (un )

1450

( )

.4 n vn

v n = u n - 1000

.5 n

= 500 ( 0,9)

.v n

.7 .
.8 .500

.u n

.1 u1 .u0
.2 .
.3 2 .3

.4 v n+1

.vn

.5 .

.6 un

vn

= u n - 1000

.v n

( )

.7 . un

.8 (un )